Sejanus albisignata its potential contribution towards apple leafcurling midge (Dasineura mali) biological control in Hawkes Bay orchards - Sharma, N.; Walker, J.T.S. (New Zealand Plant Protection, 2012)
Predation has been proposed as one of the possible reasons for the decline in apple leafcurling midge (ALCM) activity and damage observed in Hawkes Bay orchards in recent years Sejanus albisignata is a generalist predator and commonly found in apple orchards To establish if there is any relationship between ALCM and S albisignata populations of both species were monitored during 201112 on four apple orchards in Hawkes Bay Nymphs and adults of S albisignata were counted on 100 ALCM infested shoots per orchard at weekly intervals Sex pheromone traps were used to monitor numbers of male ALCM weekly throughout the season in the same orchards Sejanus albisignata and ALCM activity was well synchronized with the timing of generations one two and three of S albisignata coinciding with the second third and fourth generations of ALCM There was also a significant positive correlation between the numbers of S albisignata in each generation and the number of ALCM males trapped for each of the corresponding ALCM generations These relationships suggest that S albisignata may contribute towards ALCM control but further studies of their feeding behaviour and numerical responses are required to determine its actual contribution towards biological control of ALCM